Atretic Coronary Artery Ostia in a Full-Term Infant with Early Postnatal Demise - Choi, Nak Hyun; Piccininni, Jenna; Pollaro, Michael; Law, Sabrina; Brachio, Sandhya; Levey, Allison (Journal of Pediatric Intensive Care, 2020)
Congenital coronary artery anomalies are extremely rare causes of early cardiac failure. Several cardiac lesions are associated with coronary anomalies such as pulmonary atresia with intact ventricular septum. Isolated coronary ostial atresia is extremely rare and described in only a few published case reports. To our knowledge, there were two reports of bilateral coronary ostial atresia in which the entire coronary arterial system originated from the right ventricle without other intracardiac defects. We present a case of a full-term infant who presented with severely depressed biventricular function secondary to bilateral coronary ostial atresia.
Keywords: coronary ostial atresia; coronary; myocardial ischemia